Catalytic Cracking of Crude Palm Oil Using Ni-Carbon with Ion Exchange Method - Nazarudin Nazarudin; Ira Galih Prabasari; Agus Ari Setiawansyah; Ulyarti Ulyarti (Postgraduate, University of Mataram, 2022)
According to data from the National Energy Council (DEN) (2016), the energy consumption in Indonesia is increasing every year and will increase 1.8 times in 2025, this requires an alternative energy to back up the energy needs. One such alternative energy strategy is to use biodiesel. Biodiesel can be obtained from Crude Palm Oil using a catalytic cracking process. This study investigated the cracking of Crude Palm Oil using Ni-carbon with ion exchange method. The concentration of the metal solution used was 1, 2 and 3%, with temperature 450, 500 and 550 Â° C. The catalyst was analyzed by XRD and showed that the highest pattern at 25.6Âº on 2% solution. The catalyst characterized by SEM-EDX showed that the nickel metal bonded to the 1, 2, and 3% Ni-Charcoal catalysts was 02.01, 1.13 and 2.09%, respectively and the average of catalytic cracking product conversion at concentrations of 1, 2and 3% was 62.55, 66.52 and 56.50%, respectively.